Guarding a Perimeter Player: How to Draw an Offensive Foul/Take a Charge - Igor VuÄkoviÄ‡; Aleksandar GadÅ¾iÄ‡ (Universitas Majalengka, 2023)
The purpose of this article was to analyse an element of individual basketball technique and defensive tactics: the positioning of the defence player to take a charge. This element is not sufficiently covered in the basketball literature. The training of this element should be done in the U-16 category. The methodology of training and improvement of this element were stressed, as well as its importance and application during basketball training and matches. Coaches of younger categories must keep in mind that it is unethical to ask players to set themselves up for taking a charge without this element being thoroughly covered in training.